Efficacy and safety of PARP inhibitor maintenance therapy for ovarian cancer: a meta-analysis and trial sequential analysis of randomized controlled trials - Sun, Guojuan; Liu, Yi (Frontiers in Pharmacology, 2024)
Background: The landscape of poly (ADP-ribose) polymerase (PARP) inhibitor treatment for ovarian cancer (OC) is continually evolving. This research aimed to evaluate the efficacy and safety of PARP inhibitors compared to placebo as a maintenance therapy for OC patients. Methods: We conducted a search of PubMed, Embase, Web of Science, and the Cochrane Library databases for randomized controlled trials (RCTs) involving the use of PARP inhibitors as maintenance therapy in OC patients, up to June 16, 2024. Data regarding progression-free survival (PFS), overall survival (OS), chemotherapy-free interval (CFI), time to first subsequent therapy or death (TFST), time to second subsequent therapy or death (TSST), and treatment-emergent adverse events (TEAEs) were aggregated. Pooled hazard ratio (HR) and their corresponding 95% confidence intervals (CI) were calculated for PFS, OS, CFI, TFST, and TSST. Results: This meta-analysis encompassed 20 RCTs involving 7,832 participants. The overall analysis demonstrated that maintenance therapy with PARP inhibitors led to significant improvements in PFS (HR: 0.398, 95% CI = 0.339 to 0.467, 95% PI = 0.219 to 0.724), OS (HR: 0.677, 95% CI = 0.582 to 0.788, 95% PI = 0.546 to 0.839), CFI (HR: 0.417, 95% CI = 0.368 to 0.472, 95% PI = 0.265 to 0.627), TFST (HR: 0.441, 95% CI = 0.391 to 0.498, 95% PI = 0.308 to 0.632), and TSST (HR: 0.574, 95% CI = 0.507 to 0.649, 95% PI = 0.488 to 0.674) compared with placebo. Subgroup analyses further indicated that PARP inhibitor maintenance treatment significantly improved PFS, regardless of homologous recombination status (all p < 0.05). However, the risks of any grade (RR = 1.046, 95% CI = 1.032 to 1.059, 95% PI = 1.028 to 1.055) and grade ≥ 3 TEAEs (RR = 2.931, 95% CI = 2.641 to 3.253, 95% PI = 2.128 to 3.792) were increased by PARP inhibitor maintenance therapy compared to placebo. Conclusion: Our research elucidated the benefits of maintenance therapy with PARP inhibitors in patients with OC, showing improvements in PFS, OS, CFI, TFST, and TSST. Vigilance regarding TEAEs is paramount for clinicians implementing PARP inhibitor maintenance therapy in clinical practice.